Telaah Etika Seksual Terhadap Fenomena Perselingkuhan dalam Hubungan Monogami: Sexual Ethics Review of the Phenomenon of Infidelity in Monogamous Relationships - Panani, Sri Yulita Pramulia (Undiksha, 2024)
This research is based on the phenomenon of monogamy in Indonesian relationships. Cheating is a form of betrayal of commitment, but it is still carried out by the individual perpetrator. I mean, cheating isn't new knowledge as a bad act, but the cheater still does it. So, the purpose of this study is to describe the causes of sexual intercourse in monogamous relationships. (marital infidelity). As well as analyzing normative ethical theoretical views on acts of conspiracy in monogamous relationships. This research method is qualitative descriptive research that uses library data. The data from this research linked the material object of the phenomenon of marriage with the formal object of sexual ethics. In analysis, methodical elements include interpretation, holistic, descriptions, and critical reflection The results of this study show that marital infidelity is the first cause, which can be motivated by an unoptimal relationship and is characterized by low satisfaction, high conflict, and a lack of good communication. Other factors include sexual desire, searching for varied love, being sexually dissatisfied, angry with the partner, wanting more love and attention than the partner gives, and feeling neglected. Secondly, Kant's ethical normative deontology, consequentialism (utilitarianism, ethics egoism), and virtue ethics do not justify the acts of infidelity.